Biology of Pink Bollworm Pectinophora gossypiella (Saunders) (Gelechiidae: Lepidoptera) under Laboratory Conditions - likhitha, P.; Borkar, Archana; Kulkarni, U. S.; Undirwade, D. B.; Kolhe, A. V. (International Journal of Bio-resource and Stress Management, 2022)
The present study on biology of pink bollworm on two modified artificial diets separately was carried out in the Toxicology laboratory, Department of Agriculture Entomology, Post Graduate Institute, Dr PDKV, Akola during October to February 2018–19 and 2019–20 with controlled conditions such as 25±2oC temperature 65±5% RH and photoperiod of 14:10 h light: dark. Two modified artificial diets were prepared separately with some modifications in the ingredients, pink bollworm larvae are reared on two above said modified artificial diets and observations were recorded on different biological parameters like egg incubation period (days), larval period (days), pupal period (days), adult emergence (%), adult male and female longevity(days), preoviposition period (days), oviposition (days), fecundity(no of eggs per female), total life cycle(days) and on morphometry of different stages pink bollworm like egg, first, second, third and fourth instar larval stages, male and female pupa and male and female adult moth. Our results indicated that pink bollworm has four larval instars with mean larval duration of 18.60±0.54 days in modified artificial diet 1 and 17.72±0.36 days in modified artificial diet 2 population respectively. Total life cycle from egg to adult was 46.74±0.31 and 54.71±0.62 days in modified artificial diet 1 and modified artificial diet 2 population respectively. Total life cycle of pink bollworm was completed somewhat earlier in in modified artificial diet 1 in comparison to modified artificial diet 2. Our results showed that there was only a little difference in the biology of pink bollworm on both modified artificial diets, and hence both modified artificial diets can be used for laboratory rearing purposes.